Politics in transitional societies : the challenge of change in Asia, Africa, and Latin America - Kebschull, Harvey G.; Kebschull, Harvey G. (New York : Appleton-Century-Crofts, 1968)
No student of politics today can afford to ignore the vast regions of Asia, Africa, and Latin America. The purpose of this collection of materials is twofold: to supply some useful information on the nature of transitional societies and their problems as a foundation for more advanced study, and to sharpen the analytical skills of students of politics, whatever their foremost interests may be.
Includes bibliographical references.
Keywords: Developing countries -- Politics and government